Fear [large type] : Trump in the White House - Woodward, Bob, 1943- (Thorndike Press, a part of Gale, a Cengage Company, 2018)
Investigative reporter Bob Woodward describes life inside President Donald Trump's White House and precisely how he makes decisions on major foreign and domestic policies. Woodward draws from hundreds of hours of interviews with firsthand sources, meeting notes, personal diaries, files and documents. The focus is on the explosive debates and the decision-making in the Oval Office, the Situation Room, Air Force One and the White House residence.